THE TECHNOLOGY OF INFORMATIONAL SUPPORT OF IT-SPECIALISTS MOTIVATION MANAGING PROCESSES - Koziyakov, Sergey (Proceedings of National Aviation University (archive), 2014)
The article introduces a new informational technology of supporting IT-specialists motivation managing processes at industrial enterprises. Its architechtural decisions, the stages of informational support implementation and methods of practical using of the developed informational system are viewed.